If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7 = x + 1 Reorder the terms: 7 + 4x = x + 1 Reorder the terms: 7 + 4x = 1 + x Solving 7 + 4x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + 4x + -1x = 1 + x + -1x Combine like terms: 4x + -1x = 3x 7 + 3x = 1 + x + -1x Combine like terms: x + -1x = 0 7 + 3x = 1 + 0 7 + 3x = 1 Add '-7' to each side of the equation. 7 + -7 + 3x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 1 + -7 3x = 1 + -7 Combine like terms: 1 + -7 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 20-x=15 | | -4(f-2)=12 | | 4x-7=4x-10-3 | | 7x+12=-x^2 | | 4x^2-4x-13=0 | | 4x+5y=-9 | | 3ex+1=5 | | k/3-5=7 | | 5y/6=45 | | 4y+4=29 | | 8t-1=5 | | 99-4x=41x+19 | | 14-7x=22-14x | | 5X+X=60 | | -42-10x=10x-18 | | y^2-7y-10=0 | | 6x-7y=35 | | (x+3)(x-2)=-4 | | 222-7x=29x | | 0.4y+2(-3)=1.2 | | x^2-2x+1=22 | | x/12-7=3 | | x^2-2x=22 | | 6x+13=-19-10x | | (b/8)-12=14 | | 3(2x-5)=6x+12 | | 10-9x=102-37x | | 114-4x=5x+9 | | 2=w | | 17=-5(3+x)+7 | | -1-4x=14-9x | | 2r+32=68 |